Home My Page Projects Code Snippets Project Openings diderot

# SCM Repository

[diderot] Diff of /branches/charisee/src/compiler/high-il/normalize-ein.sml
 [diderot] / branches / charisee / src / compiler / high-il / normalize-ein.sml

# Diff of /branches/charisee/src/compiler/high-il/normalize-ein.sml

revision 2508, Tue Nov 12 17:14:33 2013 UTC revision 2608, Fri May 2 18:04:54 2014 UTC
# Line 4  Line 4
4      local      local
5
6      structure E = Ein      structure E = Ein
7  (*    structure P=Printer      structure P=Printer
8      structure O =OrderEin*)      structure F=Filter
9      in      structure G=EpsHelpers

(*Flattens Add constructor: change, expression *)
|flatten(i,((E.Const c):: l'))=
if (c>0.0 orelse c<0.0) then let
val(b,a)=flatten(i,l') in (b,[E.Const c]@a) end
else flatten(1,l')
| flatten(i,[])=(i,[])
| flatten (i,e::l') =  let
val(b,a)=flatten(i,l') in (b,[e]@a) end

val (b,a)=flatten(0,e)
in case a
of [] => (1,E.Const(1.0))
| [e] => (1,e)
(* end case *)
end
10
11        in
12
13  fun mkProd [e]=(1,e)  fun err str=raise Fail (String.concat["Ill-formed EIN Operator",str])
14      | mkProd(e)=let  val testing=1
fun flatten(i,((E.Prod l)::l'))= flatten(1,l@l')
|flatten(i,((E.Const c)::l'))=
if(c>0.0 orelse  0.0>c) then (3,[E.Const 0.0])
else flatten(i,l')
| flatten(i,[])=(i,[])
| flatten (i,e::l') =  let val(a,b)=flatten(i,l') in (a,[e]@b) end
val (change,a)=flatten(0,e)
in if(change=3) then (1,E.Const(0.0))
else case a
of [] => (1,E.Const(0.0))
| [e] => (1,e)
| es => (change, E.Prod es)
(* end case *)
end

(* filter function shifts constant/greeks to outside product*)
fun filter([],pre,dels,post)=(pre,dels,post)
| filter(E.Const c::es, pre, dels,post)=filter(es, pre@[E.Const c],dels,post)
| filter(E.Delta d::es,pre,dels,post)=filter(es,pre,dels@[E.Delta d],post)
| filter(E.Value v::es, pre, dels,post)=filter(es, pre@[E.Value v],dels,post)
| filter(E.Epsilon e::es, pre,dels, post)=filter(es, pre@[E.Epsilon e],dels,post)
| filter(E.Tensor(id,[])::es, pre, dels,post)=filter(es, pre@[E.Tensor(id,[])],dels,post)
| filter(E.Prod p::es, pre,dels, post)=filter(p@es,pre,dels,post)
| filter(e::es, pre,dels, post)= filter(es, pre, dels,post@[e])
15
16    fun flatProd [e]=e
17    | flatProd e=E.Prod e
18
19
20  fun prodPartial ([e1],p1)= E.Prod[E.Partial p1,e1]  fun prodAppPartial(es,p1)=(case es
21    | prodPartial((e1::e2),p1)=let      of []      => raise Fail "Empty App Partial"
22      val l= prodPartial(e2,p1)      | [e1]     => E.Apply(E.Partial p1,e1)
23      val (_,e2')= mkProd[e1,l]      | (e1::e2) => let
val (_,e1')=mkProd(e2@ [E.Partial p1, e1])
in
end

fun prodAppPartial ([e1],p1)= E.Apply(E.Partial p1,e1)
| prodAppPartial((e1::e2),p1)=let
24      val l= prodAppPartial(e2,p1)      val l= prodAppPartial(e2,p1)
25      val (_,e2')= mkProd[e1,l]          val (_,e2')= F.mkProd[e1,l]
26      val (_,e1')=mkProd(e2@ [E.Apply(E.Partial p1, e1)])          val (_,e1')=F.mkProd(e2@ [E.Apply(E.Partial p1, e1)])
27      in      in
29      end      end
30        (* end case *))
31
32    (*rewritten Sum*)
33    fun mkSum(c1,e1)=(case e1
34        of E.Conv _   => (0,E.Sum(c1,e1))
35  (*remove eps Index*)      | E.Field _   => (0,E.Sum(c1,e1))
36  fun rmEpsIndex(i,[],rest)=rest      | E.Probe _   => (0,E.Sum(c1,e1))
37    | rmEpsIndex(i, (E.V c ,lb, ub)::es,rest)=      | E.Apply _   => (0,E.Sum(c1,e1))
38      if (i=c) then rest@es      | E.Delta _   => (0,E.Sum(c1,e1))
39      else rmEpsIndex(i, es, rest@[(E.V c, lb, ub)])      | E.Epsilon _ => (0,E.Sum(c1,e1))
40        | E.Tensor _  => (0,E.Sum(c1,e1))
41        | E.Neg e2    => (1,E.Neg(E.Sum(c1,e2)))
42  (*remove index variable from list*)      | E.Sub (a,b) => (1,E.Sub(E.Sum(c1,a),E.Sum(c1,b)))
44      | rmIndex([],[],cs)=cs      | E.Div (a,b) => (1,E.Div(E.Sum(c1,a),E.Sum(c1,b)))
45      | rmIndex([],m ,e1::cs)=[e1]@rmIndex(m,[],cs)      | E.Lift e    => (1,E.Lift(E.Sum(c1,e)))
46      | rmIndex(i::ix,rest ,(c,lb,ub)::cs)=      | E.Sum(c2,e2)=> (1,E.Sum(c1@c2,e2))
47          if(i=c) then rmIndex(rest@ix,[],cs)      | E.Prod p     =>F.filterSca(c1,p)
48          else rmIndex(ix,rest@[i],(c,lb,ub)::cs)      | E.Const _   => err("Sum of Const")
49        | E.Partial _ => err("Sum of Partial")
50        | E.Krn _     => err("Krn used before expand")
51        | E.Value _   => err("Value used before expand")
52        | E.Img _     => err("Probe used before expand")
53  (* Transform eps to deltas*)      (*end case*))
54  fun epsToDels(E.Sum(count,E.Prod e))= let
55      fun doubleEps((E.Epsilon (a,b,c))::(E.Epsilon(d,e,f))::es,eps,e3)=  (*rewritten Apply*)
56          let  fun mkapply(d1,e1)=(case e1
57        of E.Lift e   => (1,E.Const 0)
58          (*Function is called when eps are being changed to deltas*)      | E.Prod []   => err("Apply of empty product")
59          fun createDeltas(i,s,t,u,v, e3)= let      | E.Add []    => err("Apply of empty Addition")
60        | E.Conv(v, alpha, h, d2)    =>let
61              (*remove index from original index list*)                          val E.Partial d3=d1
62                            in (1,E.Conv(v,alpha,h,d2@d3)) end
63              val s'= rmEpsIndex(i,count,[])      | E.Field _   => (0,E.Apply(d1,e1))
64        | E.Probe _   => (0,E.Apply(d1,e1))
65              val deltas= E.Sub(      | E.Apply(E.Partial d2,e2)  => let
66                      E.Prod([E.Delta(E.V s,E.V u), E.Delta(E.V t,E.V v)] @e3),                          val E.Partial d3=d1
67                      E.Prod([E.Delta(E.V s,E.V v), E.Delta(E.V t,E.V u)]@e3))                          in (1,E.Apply(E.Partial(d3@d2),e2)) end
68        | E.Apply _   => err" Apply of non-Partial expression"
69                  in (case (eps,es,s')      | E.Sum(c2,e2)=> (1,E.Sum(c2,E.Apply(d1,e2)))
70                  of ([],[],[]) =>(1,deltas)      | E.Neg e2    => (1,E.Neg(E.Apply(d1,e2)))
71                  |([],_,[]) =>(1,E.Prod( es@[deltas]))      | E.Add e     => (1,E.Add (List.map (fn(a)=>E.Apply(d1,a)) e))
72                  |([],[],_)=>(1,E.Sum(s',deltas))      | E.Sub (a,b) => (1,E.Sub(E.Apply(d1,a),E.Apply(d1,b)))
73                  |([],_,_)=>(1,E.Sum(s',E.Prod(es@[deltas])))      | E.Div (g,b) => let
|(_,_,[])=>(1,E.Prod(eps@es@[deltas]))
|_ =>(1, E.Sum(s', E.Prod(eps@es@[deltas])))
)
end

in if(a=d) then createDeltas(a,b,c,e,f, e3)
else if(a=e) then createDeltas(a,b,c,f,d, e3)
else if(a=f) then createDeltas(a,b,c,d,e, e3)
else if(b=d) then createDeltas(b,c,a,e,f, e3)
else if(b=e) then createDeltas(b,c,a,f,d,e3)
else if(b=f) then createDeltas(b,c,a,d,e,e3)
else if(c=d) then createDeltas(c,a,b,e,f,e3)
else if(c=e) then createDeltas(c,a,b,f,d,e3)
else if(c=f) then createDeltas(c,a,b,d,e,e3)
else (0,E.Const 0.0)
end
fun findeps(e,[])= (e,[])
| findeps(e,(E.Epsilon eps)::es)=  findeps(e@[E.Epsilon eps],es)
| findeps(e,es)= (e, es)

fun dist([],eps,rest)=(0,eps,rest)
| dist([e],eps,rest)=(0,eps@[e],rest)
| dist(c1::current,eps,rest)=let
val(i, exp)= doubleEps(c1::current,eps,rest)
in  (case i of 1=>(i,[exp],[E.Const 2.0])
|_=> dist(current, eps@[c1],rest))
end

val (es,rest)=findeps([],e)
74      in      in
75          dist(es,[],rest)          (case F.filterField[b]
76            of (_,[]) => (1,E.Div(E.Apply(d1,g),b)) (*Division by a real*)
77            | (pre,h) => let
78                val g'=E.Apply(d1,g)
79                val h'=E.Apply(d1,flatProd(h))
80                val num=E.Sub(E.Prod([g']@h),E.Prod[g,h'])
81                val denom=E.Prod(pre@h@h)
82                in (1,E.Div(num,denom))
83      end      end

(*Another strategy. Go through entire expression inside summation and jsut examine index to apply deltas*)

(* Apply deltas to tensors/fields*)
fun reduceDelta(E.Sum(c,E.Prod p))=let

fun findDeltas(dels,rest,E.Delta d::es)= findDeltas(dels@[E.Delta d], rest, es)
| findDeltas(dels,rest,E.Epsilon eps::es)=findDeltas(dels,rest@[E.Epsilon eps],es)
| findDeltas(dels,rest,es)=  (dels,rest,es)

fun distribute(change,d,dels,[],done)=(change,dels@d,done)
| distribute(change,[],[],e,done)=(change,[],done@e)
| distribute(change,E.Delta(i,j)::ds,dels,E.Tensor(id,[tx])::es,done)=
if(j=tx) then distribute(change@[j],dels@ds,[] ,es ,done@[E.Tensor(id,[i])])
else distribute(change,ds,dels@[E.Delta(i,j)],E.Tensor(id,[tx])::es,done)
| distribute(change,E.Delta(i,j)::ds,dels,E.Field(id,[tx])::es,done)=
if(j=tx) then distribute(change@[j],dels@ds,[] ,es ,done@[E.Field(id,[i])])
else distribute(change,ds,dels@[E.Delta(i,j)],E.Field(id,[tx])::es,done)
| distribute(change,E.Delta(i,j)::ds,dels,E.Apply(E.Partial d,e)::es,done)=
let
fun distPart([],rest) =(0 ,rest)
| distPart(p::pd,rest)=
if(p=j) then (1,rest@[i]@pd)
else (distPart(pd,rest@[p]))

val (change'',p')=distPart(d,[])
val x=print "in here "
in (case change''
of 0=>distribute(change, ds,dels@[E.Delta(i,j)], [E.Apply(E.Partial d, e)]@es,done)
|_=> distribute(change@[j], dels@ds,[], es,done@[E.Apply(E.Partial p', e)])
84              (*end case*))              (*end case*))
85          end          end
86
87                  (*      | E.Prod p =>let
88          if(j=tx) then distribute(change@[j],dels@ds,[] ,es ,done@[E.Field(id,[i])])          val (pre, post)= F.filterField p
89          else distribute(change,ds,dels@[E.Delta(i,j)],E.Field(id,[tx])::es,done)          val E.Partial d3=d1
90               *)          in F.mkProd(pre@[prodAppPartial(post,d3)])
91            end
92      | distribute(change,d,dels,e::es,done)=distribute(change,dels@d,[],es,done@[e])      | E.Const _   => err("Const without Lift")
93        | E.Tensor _  => err("Tensor without Lift")
94      val (dels,eps,es)=findDeltas([],[],p)      | E.Delta _   => err("Apply of Delta")
95      val (change,dels',done)=distribute([],dels,[],es,[])      | E.Epsilon _ => err("Apply of Eps")
96      val index=rmIndex(change,[],c)      | E.Partial _ => err("Apply of Partial")
97        | E.Krn _     => err("Krn used before expand")
98        | E.Value _   => err("Value used before expand")
99        | E.Img _     => err("Probe used before expand")
100        (*end case*))
101
in
(length change, E.Sum(index,E.Prod (eps@dels'@done)))
end
102
103    (*rewritten probe*)
104    fun mkprobe(e1,x)=(case e1
105        of E.Lift e   => (1,e)
106        | E.Prod []   => err("Probe of empty product")
107        | E.Prod p    => (1,E.Prod (List.map (fn(a)=>E.Probe(a,x)) p))
108        | E.Apply _   => (0,E.Probe(e1,x))
109        | E.Conv _    => (0,E.Probe(e1,x))
110        | E.Field _   => (0,E.Probe(e1,x))
111        | E.Sum(c,e') => (1,E.Sum(c,E.Probe(e',x)))
113        | E.Sub (a,b) => (1,E.Sub(E.Probe(a,x),E.Probe(b,x)))
114        | E.Neg e'    => (1,E.Neg(E.Probe(e',x)))
115        | E.Div (a,b) => (1,E.Div(E.Probe(a,x),E.Probe(b,x)))
116        | E.Const _   => err("Const without Lift")
117        | E.Tensor _  => err("Tensor without Lift")
118        | E.Delta _   => err("Probe of Delta")
119        | E.Epsilon _ => err("Probe of Eps")
120        | E.Partial _ => err("Probe Partial")
121        | E.Probe _   => err("Probe of a Probe")
122        | E.Krn _     => err("Krn used before expand")
123        | E.Value _   => err("Value used before expand")
124        | E.Img _     => err("Probe used before expand")
125    (*end case*))
126
(*Apply Sum*)
fun mkApplySum(E.Apply(E.Partial d,E.Sum(c,e)))=(case e
of E.Tensor(a,[])=>(1,E.Const 0.0)
| E.Const _ =>(1,E.Const 0.0)
| E.Delta _ =>(1,E.Const 0.0)
| E.Value _ =>(1,E.Const 0.0)
| E.Epsilon _ =>(1,E.Const 0.0)

| E.Add l => (1,E.Add(List.map (fn e => E.Apply(E.Partial d, E.Sum(c,e))) l))
| E.Sub(e2, e3) =>(1, E.Sub(E.Apply(E.Partial d, E.Sum(c,e2)), E.Apply(E.Partial d, E.Sum(c,e3))))
| E.Conv (fid,alpha,tid, delta)=> let
val e'=E.Conv(fid,alpha, tid, delta@d)
in (1,E.Sum(c,e')) end

| E.Prod [e1]=>(1,E.Apply(E.Partial d,E.Sum(c,e1)))
| E.Prod es'=> let
val y=print "in apply sum"
val (change,m)=reduceDelta(E.Sum(c,e))
val t=print(Int.toString(change))
val (sumc,es)=(case (change,m) of (0,_)=>(c,es')
| (_,E.Sum( c', E.Prod p)) =>(c',p)
(*end case*))
val (pre', dels,post)= filter(es,[],[],[])
val pre=pre'@dels
val x1= prodAppPartial(post,d)
in  (case x1
| _ => (1,E.Sum(sumc, E.Prod(pre@[x1])))
(*end case*))
end
|_=>(0,E.Apply(E.Partial d,E.Sum(c,e)))
(* end case*))

(*Apply*)
fun mkApply(E.Apply(E.Partial d,e))=(case e
of E.Tensor(a,[])=>(1,E.Const 0.0)
| E.Const _ =>(1,E.Const 0.0)
| E.Delta _ =>(1,E.Const 0.0)
| E.Value _ =>(1,E.Const 0.0)
| E.Epsilon _ =>(1,E.Const 0.0)
| E.Conv (fid,alpha,tid, delta)=> let
val e'=E.Conv(fid,alpha, tid, delta@d)
in (1,e') end
| E.Add l => (1,E.Add(List.map (fn e => E.Apply(E.Partial d, e)) l))
| E.Sub(e2, e3) =>(1, E.Sub(E.Apply(E.Partial d, e2), E.Apply(E.Partial d, e3)))
| E.Div(e2, e3) =>(1, E.Div(E.Apply(E.Partial d, e2),  e3))
| E.Apply(E.Partial d2,e2)=>(1,E.Apply(E.Partial(d@d2), e2))
| E.Prod [e1]=>(1,E.Apply(E.Partial d,e1))
| E.Prod es=> let
val (pre,dels, post)= filter(es,[],[],[])
val (_,x)=mkProd(pre@[prodAppPartial(post,d)])
in (1,x) end
|_=>(0,E.Apply(E.Partial d,e))
(* end case*))

(*Sum Apply*)

fun matchEps(2,_,_,_)= 1 (*matched 2*)
| matchEps(num,_,_,[])=0
| matchEps(0,_,_,[eps])=0
| matchEps(num,[],rest,eps::epsx)=
matchEps(num,rest,[],epsx)
| matchEps(num,E.V p::px,rest,eps::epsx)=
if(p=eps) then (matchEps(num+1,rest@px,[],epsx))
else matchEps(num,px,rest@[E.V p], eps::epsx)
| matchEps(num,p::px,rest,eps)=
matchEps(num,px,rest,eps)

fun mkSumApply(E.Sum(c,E.Apply(E.Partial d,e)))=(case e
of E.Const _=>(1,E.Const 0.0)
| E.Tensor(_,[])=> (1,E.Const 0.0)
| E.Delta _ =>(1,E.Const 0.0)
| E.Value _ =>(1,E.Const 0.0)
| E.Epsilon _ =>(1,E.Const 0.0)
| E.Conv (fid,alpha,tid, delta)=> let
val e'=E.Conv(fid,alpha, tid, delta@d)
in (1,E.Sum(c,e')) end
| E.Apply(E.Partial d1,e2)=>(1,E.Sum(c,E.Apply(E.Partial(d@d1),e2)))
| E.Add l => (1,E.Add(List.map (fn e => E.Sum(c,E.Apply(E.Partial d, e))) l))
| E.Sub(e1, e2) => (1, E.Sub(E.Sum(c,E.Apply(E.Partial d, e1)), E.Sum(c,E.Apply(E.Partial d, e2))))

| E.Prod [e1]=>(1,E.Sum(c,E.Apply(E.Partial d,e1)))

| E.Prod(E.Tensor(a,[])::e2)=>(1, E.Prod[E.Tensor(a,[]),E.Sum(c,E.Apply(E.Partial d,E.Prod e2))])

| E.Prod es =>(let
fun prod (change,rest, sum,partial,[]) = (change,E.Sum(sum,E.Apply(E.Partial partial,E.Prod rest)))
| prod (change,rest, sum,partial,E.Epsilon(i,j,k)::ps)= let
val change'= matchEps(0,d,[],[i,j,k])
in (case change'
of 1 => (1,E.Const 0.0)
| _ =>prod(change,rest@[E.Epsilon(i,j,k)],sum,partial,ps)
(*end case*))
end
| prod (change,rest, sum,partial,E.Delta(i,j)::ps)=let
fun applyDelPartial([],_)=(0,[])
| applyDelPartial(p::px,r)=
if(j=p) then (1,r@[i]@px)
else  applyDelPartial(px,r@[p])

val (change',px)=applyDelPartial(d,[])

in (case change'
of 1 => (let val index=rmIndex([j],[],sum)
in prod(1,rest, index,px, ps) end )
| _ => prod(change,rest@[E.Delta(i,j)], sum,partial, ps)
(*end case*)) end
127
| prod (change,rest,sum, partial,e::es)= prod(change,rest@[e],sum,partial,es)
128
in  prod(0,[],c, d, es)
129
130
131          end)  (*fun K gg=String.concatWith "," (List.map (fn (E.V e1,_,_)=> (Int.toString(e1))) gg)*)
132          | _=>(0,E.Sum(c,E.Apply(E.Partial d,e)))  fun K _= " "
133          (* end case*))  fun Kt gg=List.map (fn e1=> print(String.concat["[", (K e1),"]"])) gg

134
135  (*Apply normalize to each term in product list  (*Apply normalize to each term in product list
136  or Apply normalize to tail of each list*)  or Apply normalize to tail of each list*)
137  fun normalize (Ein.EIN{params, index, body}) = let  fun normalize (Ein.EIN{params, index, body}) = let
138         (* val _ = print(String.concat["\n IN NORMALIZE@", P.printbody(body),"@\n"])*)
139        val changed = ref false        val changed = ref false
140          val sumIndex=ref []
141
142        fun rewriteBody body = (case body        fun rewriteBody body = (case body
143               of E.Const _=> body               of E.Const _=> body
144                | E.Tensor _ =>body                | E.Tensor _ =>body
145                | E.Field _=> body                | E.Field _=> body
146                | E.Delta _ => body                | E.Delta _ => body
| E.Value _ =>body
147                | E.Epsilon _=>body                | E.Epsilon _=>body
148                | E.Conv _=>body                | E.Conv _=>body
149                | E.Partial _   => body
150                | E.Krn _       => raise Fail"Krn before Expand"
151                | E.Img _       => raise Fail"Img before Expand"
152                | E.Value _     => raise Fail"Value before Expand"
153
154                    (*************Algebraic Rewrites **************)
155                | E.Neg(E.Neg e)    => rewriteBody e
156                | E.Neg e => E.Neg(rewriteBody e)                | E.Neg e => E.Neg(rewriteBody e)
157                | E.Add es => let val (change,body')= mkAdd(List.map rewriteBody es)              | E.Lift e          => E.Lift(rewriteBody e)
159                     in if (change=1) then ( changed:=true;body') else body' end                     in if (change=1) then ( changed:=true;body') else body' end
160                  | E.Sub(a, E.Field f)=> (changed:=true;E.Add[a, E.Neg(E.Field(f))])                  | E.Sub(a, E.Field f)=> (changed:=true;E.Add[a, E.Neg(E.Field(f))])
164                | E.Sub (a,b)=>  E.Sub(rewriteBody a, rewriteBody b)                | E.Sub (a,b)=>  E.Sub(rewriteBody a, rewriteBody b)
165                | E.Div(E.Div(a,b),E.Div(c,d))  => rewriteBody(E.Div(E.Prod[a,d],E.Prod[b,c]))
166                | E.Div(E.Div(a,b),c)           => rewriteBody (E.Div(a, E.Prod[b,c]))
167                | E.Div(a,E.Div(b,c))           =>  rewriteBody (E.Div(E.Prod[a,c],b))
168                | E.Div (a, b) => E.Div(rewriteBody a, rewriteBody b)                | E.Div (a, b) => E.Div(rewriteBody a, rewriteBody b)
| E.Partial _=>body
| E.Krn(tid,deltas,pos)=> E.Krn(tid,deltas, (rewriteBody pos))
| E.Img(fid,alpha,pos)=> E.Img(fid,alpha, (List.map rewriteBody pos))
169
170                    (**************Apply, Sum, Probe**************)
171                | E.Apply(E.Partial [],e)=> e
172                | E.Apply(E.Partial d1, e1)=>let
173                    val e2 = rewriteBody e1
174                    val (c,e3)=mkapply(E.Partial d1,e2)
175                    in (case c of 1=>(changed:=true;e3)| _ =>e3 (*end case*))
176                    end
177                | E.Apply _=> raise Fail" Not well-formed Apply expression"
178                | E.Sum([],e)=> (changed:=true;rewriteBody e)
179                | E.Sum(c,e)=>let
180                    val ref x=sumIndex
181                    val c'=[c]@x
182                    val e'=(sumIndex:=c';rewriteBody e)
183                    val ref s=sumIndex
184                    val z=hd(s)
185                    val (cng,e2)=(sumIndex:=tl(s);mkSum(z,e'))
186                    in (case cng
187                        of 1=> (changed:=true;e2)
188                        |_=> e2
189                        (*end case*))
190                    end
191                  | E.Probe(u,v)=>  let
192                    val (c',b')=mkprobe(rewriteBody u,rewriteBody v)
193                    in (case c'
194                        of 1=> (changed:=true;b')
195                        |_=> b'
196                        (*end case*))
197                    end
198
199                  (*************Product**************)                  (*************Product**************)
200                  | E.Prod [] => raise Fail"missing elements in product"
201                | E.Prod [e1] => rewriteBody e1                | E.Prod [e1] => rewriteBody e1
203                     (changed := true; E.Add(List.map (fn e=> E.Prod([e]@e3)) e2))                     (changed := true; E.Add(List.map (fn e=> E.Prod([e]@e3)) e2))
204                | E.Prod((E.Sub(e2,e3))::e4)=>                | E.Prod((E.Sub(e2,e3))::e4)=>
205                     (changed :=true; E.Sub(E.Prod([e2]@e4), E.Prod([e3]@e4 )))                     (changed :=true; E.Sub(E.Prod([e2]@e4), E.Prod([e3]@e4 )))
206                  | E.Prod((E.Div(e2,e3))::e4)=> (changed :=true; E.Div(E.Prod([e2]@e4), e3 ))
| E.Prod((E.Div(e2,e3))::e4)=>
(changed :=true; E.Div(E.Prod([e2]@e4), e3 ))

208                  (changed := true; E.Add(List.map (fn e=> E.Prod([e1,e]@e3)) e2))                  (changed := true; E.Add(List.map (fn e=> E.Prod([e1,e]@e3)) e2))
209                | E.Prod(e1::E.Sub(e2,e3)::e4)=>                | E.Prod(e1::E.Sub(e2,e3)::e4)=>
210                  (changed :=true; E.Sub(E.Prod([e1,e2]@e4), E.Prod([e1,e3]@e4 )))                  (changed :=true; E.Sub(E.Prod([e1,e2]@e4), E.Prod([e1,e3]@e4 )))
211
212
213
214                    (*************Product EPS **************)
215
216                | E.Prod(E.Epsilon(i,j,k)::E.Apply(E.Partial d,e)::es)=>let                | E.Prod(E.Epsilon(i,j,k)::E.Apply(E.Partial d,e)::es)=>let
217                   val change= matchEps(0,d,[],[i,j,k])                   val change= G.matchEps(0,d,[],[i,j,k])
218                   in case (change,es)                   in case (change,es)
219                  of (1,_) =>(changed:=true; E.Const 0.0)                  of (1,_) =>(changed:=true; E.Const 0)
220                      | (_,[]) =>E.Prod[E.Epsilon(i,j,k),                      | (_,[]) =>E.Prod[E.Epsilon(i,j,k),rewriteBody (E.Apply(E.Partial d,e))]
(rewriteBody (E.Apply(E.Partial d,e)))]
221                      |(_,_)=> let                      |(_,_)=> let
222                          val a=rewriteBody(E.Prod([E.Apply(E.Partial d,e)]@ es))                          val a=rewriteBody(E.Prod([E.Apply(E.Partial d,e)]@ es))
223                          val (_,b)=mkProd [E.Epsilon(i,j,k),a]                          val (_,b)=F.mkProd [E.Epsilon(i,j,k),a]
224                          in b end                          in b end
225                  end                  end
226                | E.Prod[(E.Epsilon(e1,e2,e3)), E.Tensor(_,[E.V i1,E.V i2])]=>                | E.Prod(E.Epsilon(i,j,k)::E.Conv(V,alpha, h, d)::es)=>let
if(e2=i1 andalso e3=i2) then (changed :=true;E.Const(0.0))
else body
| E.Prod [E.Partial r1, E.Tensor(_,[])]=> (changed:=true;E.Const(0.0))
| E.Prod [E.Partial r1,E.Partial r2]=>
(changed:=true;E.Partial(r1@r2))
227
228                | E.Prod(E.Partial r1::E.Partial r2::p)=>                  val change= G.matchEps(0,d,[],[i,j,k])
229                      (changed:=true;E.Prod([E.Partial(r1@r2)]@p))                  in case (change,es)
230                | E.Prod(E.Sum(c1,E.Prod(E.Epsilon e1::es1))::E.Sum(c2,E.Prod(E.Epsilon e2::es2))::es)=>let                      of (1,_) =>(changed:=true; E.Const 0)
231                    val (change,e,rest)=epsToDels(E.Sum(c1@c2, E.Prod([E.Epsilon e1, E.Epsilon e2]@es1@es2@es)))                      | (_,[]) =>E.Prod[E.Epsilon(i,j,k),E.Conv(V,alpha, h, d)]
232                  in (case (change,e, rest)                      | (_,_) =>let
233                      of (1,[e1],_)=> (changed:=true;e1)                          val a=rewriteBody(E.Prod([E.Conv(V,alpha, h, d)]@ es))
234                      | _=>let                          val (_,b) = F.mkProd [E.Epsilon(i,j,k),a]
235                          val e1=rewriteBody(E.Sum(c1,E.Prod(E.Epsilon e1::es1)))                          in b end
val es'=rewriteBody(E.Prod(E.Sum(c2,E.Prod(E.Epsilon e2::es2))::es))
val (_,e)=(case es' of E.Prod p=>mkProd([e1]@p)
|_=> mkProd([e1]@e)
(*end case*))
in e
end
(*end case*))
end
| E.Prod[e1,e2]=> let val (_,b)=mkProd[rewriteBody e1, rewriteBody e2] in b end
| E.Prod(e::es)=>let
val e'=rewriteBody e
val e2=rewriteBody(E.Prod es)
val(_,b)=(case e2
of E.Prod p'=> mkProd([e']@p')
|_=>mkProd [e',e2])
in b
236                     end                     end
237
(**************Apply**************)
238
239                (* Apply, Sum*)                | E.Prod[(E.Epsilon(e1,e2,e3)), E.Tensor(_,[E.V i1,E.V i2])]=>
240                | E.Apply(E.Partial d,E.Sum e)=>let                      if(e2=i1 andalso e3=i2) then (changed :=true;E.Const(0))
241                      val s'=rewriteBody(E.Sum  e)                      else body
val (c, e')=(case s'
of E.Sum e1=> mkApplySum(E.Apply(E.Partial d,s'))
| _=>(0, E.Apply(E.Partial d, s'))
(*end case*))
in (case c
of 1=>(changed:=true;e')
|_=> e'
(*end case*))
end

| E.Apply(E.Partial [],e)=> e
| E.Apply(E.Partial p,E.Probe(E.Conv(fid,alpha,tid,d),x))=>
(changed:=true;E.Probe(E.Conv(fid,alpha,tid,d@p),x))
| E.Apply(E.Partial p,E.Conv(fid,alpha,tid,d))=>
(changed:=true;E.Conv(fid,alpha,tid,d@p))
| E.Apply(E.Partial p, e)=>let

val body'=E.Apply(E.Partial p, rewriteBody e)
val (c, e')=mkApply(body')
in (case c
of 1=>(changed:=true;e')
| _ =>e') end
242
| E.Apply(e1,e2)=>((E.Apply(rewriteBody e1, rewriteBody e2))
)
243
244                | E.Prod(E.Epsilon eps1::ps)=>
245                    let
246
247                (************** Sum *****************)                  val ref x=sumIndex
248                | E.Sum([],e)=> (changed:=true;rewriteBody e)                  val (i,s',e,rest)=G.epsToDels(x,body)
| E.Sum(_,E.Const c)=>(changed:=true;E.Const c)
| E.Sum(c,E.Sub(e1,e2))=>(changed:=true; E.Sub(E.Sum(c,e1),E.Sum(c,e2)))
| E.Sum(c,E.Div(e1,e2))=>(changed:=true; E.Div(E.Sum(c,e1),E.Sum(c,e2)))
| E.Sum(c, E.Prod(E.Const e::es))=>(changed:=true;E.Prod[E.Const e,E.Sum(c, E.Prod es)])

| E.Sum(c, E.Prod(E.Value v::es))=>(changed:=true; E.Prod [E.Value v, E.Sum(c, E.Prod es)])
| E.Sum(c, E.Prod(E.Tensor(id,[])::es))=> (changed:=true;E.Prod [E.Tensor(id,[]), E.Sum(c, E.Prod es)])
| E.Sum(c,E.Prod(E.Epsilon eps1::E.Epsilon eps2::ps))=>
let val (i,e,rest)=epsToDels(body)
249                  in (case (i, e,rest)                  in (case (i, e,rest)
250                      of (1,[e1],r) =>(changed:=true;e1)                  of (1,[e1],_) =>(changed:=true;sumIndex:=s';e1)
251                      |(0,eps,[])=>body                      |(0,eps,[])=>body
252                      |(0,eps,rest)=> let                      | _ => let
253                          val p'=rewriteBody(E.Prod rest)                          val p'=rewriteBody(E.Prod rest)
254                          val p''= (case p' of E.Prod p=>p |e=>[e])                          val p''= (case p' of E.Prod p=>p |e=>[e])
255                          val(_,b)= mkProd (eps@p'')                          val(_,b)= F.mkProd (e@p'')
256                          in E.Sum(c,b) end                          in b end
|_=>body
257                      (*end case*))                      (*end case*))
258                     end                     end
259                | E.Prod(E.Sum(c1,E.Prod(E.Epsilon e1::es1))::E.Sum(c2,E.Prod(E.Epsilon e2::es2))::es)=>let
260                    val ref x=sumIndex
261
262
263                    val m= Kt x
264
265                    val c'= [c1@c2]@x
266                    val (i,s',e,rest)=G.epsToDels(c', E.Prod([E.Epsilon e1, E.Epsilon e2]@es1@es2@es))
267                     val gsg=Kt s'
268
269
| E.Sum(c1,E.Prod(E.Epsilon eps1::E.Sum(c2,E.Prod(E.Epsilon eps2::s2))::ps))=>let
val (i, e, rest)=epsToDels(E.Sum(c1@c2, E.Prod([E.Epsilon eps1, E.Epsilon eps2]@ s2@ps)))
270                    in (case (i,e,rest)                    in (case (i,e,rest)
271                      of (1,[e1],_) =>(changed:=true; e1)                      of (1,[e1],_)=> (changed:=true;sumIndex:=s';let
272                      |_ => E.Sum(c1,rewriteBody(E.Prod(E.Epsilon eps1::E.Sum(c2,E.Prod(E.Epsilon eps2::s2))::ps)))                          val ss=List.nth(s',((length s')-2))
273                            in
274                                E.Sum(ss,e1) end )
275                        | _=>let
276                            val eA=rewriteBody(E.Sum(c1,E.Prod(E.Epsilon e1::es1)))
277                            val eB=rewriteBody(E.Prod(E.Sum(c2,E.Prod(E.Epsilon e2::es2))::es))
278                            val (_,e)=F.mkProd([eA,eB])
279                            in e
280                            end
281                      (* end case*))                      (* end case*))
282                    end                    end
283
284                | E.Sum(c,E.Prod(E.Delta d::es))=>let              | E.Prod(E.Delta d::es)=>let
285                      val (change,a)=reduceDelta(body)                  val (pre',eps, dels,post)= F.filterGreek(E.Delta d::es)
286                    val ref x=sumIndex
287                    val (change,i',a)=G.reduceDelta(x, eps, dels, post)
288
289                      in (case (change,a)                      in (case (change,a)
290                  of (0, _)=> E.Sum(c,rewriteBody(E.Prod([E.Delta d]@es)))                      of (0, _)=> E.Prod [E.Delta d,rewriteBody(E.Prod es)]
291                          | (_, E.Prod p)=>let                          | (_, E.Prod p)=>let
292                              val (_, p') = mkProd p                          val (_, p') = F.mkProd p
293                              in (changed:=true;p') end                          in (changed:=true;sumIndex:=i';p') end
294                          | _ => (changed:=true;a )                      | _ => (changed:=true;sumIndex:=i';a )
295                          (*end case*))                          (*end case*))
296                      end                      end
297
298                  | E.Prod[e1,e2]=> let val (_,b)=F.mkProd[rewriteBody e1, rewriteBody e2] in b end
299                | E.Sum(c,E.Apply(E.Partial p,e))=>let                | E.Prod(e::es)=>let
300                      val (change,exp)=mkSumApply(body)                      val e'=rewriteBody e
301                      val exp'=(case change                      val e2=rewriteBody(E.Prod es)
302                          of 1=> (changed:=true;exp)                      val(_,b)=(case e2
303                          | _ => E.Sum(c,rewriteBody(E.Apply(E.Partial p,e))))                          of E.Prod p'=> F.mkProd([e']@p')
304                      in exp' end                          |_=>F.mkProd [e',e2])
305                    in b

| E.Sum(c,e)=>E.Sum(c,rewriteBody e)

(*Probe*)
| E.Probe(E.Sum(c,s),x)=>(changed:=true;E.Sum(c,E.Probe(s,x)))
| E.Probe(E.Neg e1,x)=>(changed:=true;E.Neg(E.Probe(e1,x)))
| E.Probe(E.Sub (a,b),x)=>
(changed:=true;E.Sub(rewriteBody(E.Probe(a,x)), rewriteBody(E.Probe(b,x))))
| E.Probe(E.Div (a,b),x) =>
(changed:=true;E.Div(rewriteBody(E.Probe(a, x)),b))
| E.Probe(E.Prod p, x)=>let
val (p',x')= (rewriteBody (E.Prod p), rewriteBody x)
fun  probeprod([],rest) =
(print "err-Did not find field/Conv"; body)
| probeprod(E.Const c::es,rest)=
(changed:=true;probeprod(es,rest@[E.Const c]))
| probeprod(E.Tensor t::es,rest)=
(changed:=true;probeprod(es,rest@[E.Tensor t]))
| probeprod(E.Krn e::es, rest)=
(changed:=true;probeprod(es, rest@[E.Krn e]))
| probeprod(E.Delta e::es, rest)=
(changed:=true;probeprod(es, rest@[E.Delta e]))
| probeprod(E.Value e::es, rest)=
(changed:=true;probeprod(es, rest@[E.Value e]))
| probeprod(E.Epsilon e::es, rest)=
(changed:=true;probeprod(es, rest@[E.Epsilon e]))
| probeprod(E.Partial e::es, rest)=
(changed:=true;probeprod(es, rest@[E.Partial e]))
| probeprod(E.Field f::es,rest)=
(changed:=true;E.Prod(rest@[E.Probe(E.Field f, x')] @es))
| probeprod(E.Conv f::es,rest)=
(changed:=true;E.Prod(rest@[E.Probe(E.Conv f, x')] @es))
| probeprod(E.Prod p::es , rest)=
(changed:=true;probeprod(p@es,rest))
| probeprod(_,[])=body
| probeprod(e1::es, rest)=let
val e'= rewriteBody(E.Prod(e1::es))
val e''= rewriteBody(E.Probe(e',x'))
in  (changed:=true;E.Prod(rest@[e'']))
end
in (case p'
of E.Prod pro=>probeprod(p,[])
|_=> E.Probe(p',x')
(*end case*))
306                  end                  end
307                  | E.Probe(u,v)=>  (E.Probe(rewriteBody u, rewriteBody v))
308              (*end case*))              (*end case*))
309
310        fun loop(body ,count) = let        fun loop(body ,count) = let
311              val body' = rewriteBody body              val body' = rewriteBody body
312
(* val y=(print "Counter:";print(Int.toString(count));print"\n")*)
313              in              in
314                if !changed                if !changed
315                  then (changed := false ;loop(body',count+1))                  then let
316                        val _= (case testing
317                            of 1=> (print(String.concat["\nN =>",Int.toString(count),"--",P.printbody(body')]);1)
318                            | _=> 1)
319                        in
320                            (changed := false ;sumIndex:=[];loop(body',count+1))
321                        end
322                  else (body',count)                  else (body',count)
323              end              end
324
325      val (b,count) = loop(body,0)      val (b,count) = loop(body,0)
326      (*val j=(print "Final Counter:";print(Int.toString(count));print"\n")*)      val _ =(case testing
327            of 1 => (print(String.concat["\n out of normalize \n",P.printbody(b),"\n    Final CounterXX:",Int.toString(count),"\n\n"]);1)
328            | _=> 1
329            (*end case*))
330      in      in
331                  (Ein.EIN{params=params, index=index, body=b},count)                  (Ein.EIN{params=params, index=index, body=b},count)
332      end      end

Legend:
 Removed from v.2508 changed lines Added in v.2608